Cross-Cultural Mentoring in Counselor Education: A Call to Action - Marianna L Oller; Sunny S Teeling (Teaching and Supervision in Counseling, 2021)
Given the lack of formalized cross-cultural mentorship guidelines within professional counseling associations and accreditation programs, the recruitment and retention of marginalizedgraduate students, may be in jeopardy. The authors explored the value of mentoring for graduate students, the exponential growth rate of diversity within graduate programs, and how the disparity of marginalized faculty members creates a need and opportunity for cross-cultural mentorship. Recommendations for the creation of holistic cross-culturalmentorship guidelines for faculty-studentdyads are provided.
Keywords: cross-cultural; mentoring; counselor education; marginalized students